2019
DOI: 10.1371/journal.pone.0220637
|View full text |Cite
|
Sign up to set email alerts
|

Right-to-left shunts and hormonal therapy influence cerebral vasomotor reactivity in patients with migraine with aura

Abstract: Patent Foramen Ovale and impaired cerebral hemodynamics were proposed among the pathophysiological mechanisms explaining the increased risk for stroke in patients with Migraine with Aura (MA). Our study aimed at comparing the vasomotor reactivity (VMR) of the anterior and the posterior cerebral circulation in patients with Migraine with Aura, in patients with acute vascular ischemic accidents, and in controls. We hypothesized that VMR in MA patients is preserved in the anterior circulation and reduced in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
1
18
0
1
Order By: Relevance
“…However, previous studies demonstrated that patients with migraine with aura might have excessive response to several stimuli ( 20 , 21 ). Further studies are needed to investigate the CGRP induced differences between migraine with aura and migraine without aura ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies demonstrated that patients with migraine with aura might have excessive response to several stimuli ( 20 , 21 ). Further studies are needed to investigate the CGRP induced differences between migraine with aura and migraine without aura ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Peculiar cerebral and peripheral hemodynamics profiles (23,26) and increased stroke risk (38) differentiate these patients from those without aura. Specifically, migraineurs with aura seem to present a more reactive cerebral and peripheral vascular tree (12,23,26). At the moment, it cannot be ruled out that this hyperactive vascular system may be more prone to the inhibition of the CGRP pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The breath-holding index (BHI) was calculated by dividing the percent increase in mean flow velocity (MFV) occurring during breath holding by the time (30 sec) the subjects held their breath after a normal inspiration ([MFV at the end of breath-holding−rest MFV/rest MFV] × 100/sec of breath holding). The mean BHI observed in other cohorts of healthy subjects is around 1.5%/sec (23); wheareas a cutoff value of less than 0.69%/sec has clearly been demonstrated to have a high predictive value for cerebrovascular disease (24).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitric oxide super-sensitivity of the cerebral circulation has been consistently demonstrated in migraineurs (endothelial and parasympathetic control) ( 8 ). Similarly, migraine patients, in particular those with migraine with aura (MA), can display a higher response to hypercapnia (i.e., vasomotor reactivity, metabolic control) ( 9 , 10 ). Finally, the vascular tree of MA patients is also more reactive to sensory inputs such as visual stimulation (i.e., neurovascular coupling) ( 11 ).…”
mentioning
confidence: 99%